Analysis of Cultural Factors at Santo Thomas 2 Medan Catholic Private Elementary School, 2022/2023 Academic Year - Febriella Happy; Antonius Remigius Abi; Nova Florentina Ambarwati (International Journal of Educational and Psychological Sciences, 2023)
This research aims to analyze school cultural factors at the Santo Thomas 2 Medan Catholic Private Elementary School. The method used in this research is qualitative with a case study approach, with data collection in the form of interviews, observation and documentation. The results of this research show that so far the implementation of school culture at the Santo Thomas 2 Medan Catholic Private Elementary School has been implemented well. There are several things that can support the successful implementation of school culture, including the existing infrastructure at the Santo Thomas 2 Medan Catholic Private Elementary School which is quite complete and adequate, the role of parents who provide support in the form of material support (students' needs) and non-material support (in the form of love, attention, responsibility, enthusiasm and motivation) for students, by creating a conducive environment can be a supporting factor in the successful implementation of school culture, forming disciplined and focused school management can support the success of business culture, the attitude of students who are active in carrying out activities that blend school culture and the attitudes of teachers who have discipline and responsibility in implementing school culture.